2019
DOI: 10.1523/eneuro.0047-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Imaging Reveals Aberrant Functional Connectome Organization and Elevated Dorsal StriatalArcExpression in Advanced Age

Abstract: The functional connectome reflects a network architecture enabling adaptive behavior that becomes vulnerable in advanced age. The cellular mechanisms that contribute to altered functional connectivity in old age, however, are not known. Here we used a multiscale imaging approach to link age-related changes in the functional connectome to altered expression of the activity-dependent immediate-early gene Arc as a function of training to multitask on a working memory (WM)/biconditional association task (BAT). Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 100 publications
(145 reference statements)
4
28
0
Order By: Relevance
“…It is well established that the frequency bandwidth of spontaneous BOLD signal oscillations falls within previously characterized infraslow frequencies (<0.5) that cover a large expanse of rat cortex (60,61). Studies in primate visual cortex have also shown that normalized spectral frequencies in the band limited power for gamma (40-100Hz) share a high degree of statistical dependency (mutual information) with the fMRI BOLD signal while alpha (8)(9)(10)(11)(12) Hz), beta (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and higher frequency (0.9-3kHz) multi-unit activity much less so (62).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…It is well established that the frequency bandwidth of spontaneous BOLD signal oscillations falls within previously characterized infraslow frequencies (<0.5) that cover a large expanse of rat cortex (60,61). Studies in primate visual cortex have also shown that normalized spectral frequencies in the band limited power for gamma (40-100Hz) share a high degree of statistical dependency (mutual information) with the fMRI BOLD signal while alpha (8)(9)(10)(11)(12) Hz), beta (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and higher frequency (0.9-3kHz) multi-unit activity much less so (62).…”
Section: Discussionmentioning
confidence: 81%
“…The paradigm used here did not generate a memory 'response' by the rats prior or after scanning and this weakens the direct linkage between the network differences between groups and their role in memory structure in the brain. Regarding the experimental paradigm itself, we have previously applied better validated and more system selective experimental paradigms for assessing learning and memory that allowed a priori hypothesis testing of the brain regions involved in memory processing (20,21). We anticipate future studies using similar paradigms here but with the added modification that the memory-retrieving process or the memory-signaling behavior be carried out or measured during a short temporal delay prior to imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Performance on the MWM in aged male rats correlates with strength of default mode connectivity with the retrosplenial cortex 16 , and weakening of CA1-prefrontal connectivity is associated age-related decline in learning 17 . An index of rich club organization, which reflects the presence of a small group of very high degree ‘hub’ nodes, was observed to be greater in aged versus young male rats, and increased as a function of cognitive training 18 . Longitudinal decline in memory was linked to changes in functional connectivity between the dorsal hippocampus and retrosplenial cortex, thalamus, striatum, and amygdala 19 .…”
Section: Introductionmentioning
confidence: 94%